Variability of Upper Winds over India (MAUSAM, 1961)
Information about the normal upper winds as well as their variability with respect to direction and speed are useful factors for aviators.  Based on normal upper winds at the pibal stations in India and neighbourhood, the steadiness factor and the standard vector deviation have been computed at selected levels for four typical months, January, April, July and October.  Charts depicting these parameters have been prepared and the results discussed.